Cultural Dietary Norms and Associated Factors in an Urban-Dwelling Chinese American Community Sample (P04-129-19). (13th June 2019) - Wong, Jennifer; Russo, Rienna; Min, Deborah; Ah-Yune, Judy; Kwon, Simona; Yi, Stella
Abstract: Objectives: To assess prevalence of dietary cultural norms (consumption of brown rice, raw vegetables, low sodium diet) and the association of acculturation level with these norms in a Chinese American sample in New York City (NYC). Methods: We conducted a cross-sectional survey (2018 Examining Norms and Behaviors Linked to Eating [ENABLE] Pilot Study) among urban-dwelling Chinese immigrant communities in NYC ( n = 239). Multivariable models predicted the effect of acculturation on three dimensions of Chinese cultural dietary norms: non-consumption of raw vegetables, brown rice, and low sodium diet, adjusted for age and sex. Acculturation dimensions were defined as both identification with ethnic society (Chinese culture) immersion (ESI) and with dominant society (American culture) immersion (DSI); maximum possible scores = 4. STATA was used for all analyses. Results: The majority of the sample identified strongly with Chinese culture (73% above mean ESI = 3.2) and less with American culture (55% below mean DSI = 3.0). Overall, participation in dietary norms was low across the three dimensions; 21% reported not consuming raw vegetables; 37% not consuming brown rice; and 41% not consuming low sodium diets. Participants with higher acculturation to American society (DSI > 3.0) had lower participation in raw vegetable and brown rice dietary norms; 7% for raw vegetables, and 22% for brown rice. Those more acculturated to American culture were more likely to report consumption of brown rice (aOR = 3.57, 95% CI 0.01–12.50). Having a college education or higher was associated with reduced likelihood of participating in raw vegetable norms (aOR = 0.21, 95% CI 0.08–0.51) and brown rice norms (aOR = 0.46, 95% CI 0.22–0.98). No associations were found between ESI and participating in any dietary norms using univariate or multivariate models. Conclusions: Immersion into American society and education may be more influential on norms than traditional beliefs while acculturation to American society appears to dissuade participation in traditional Chinese dietary norms – specifically, consumption of brown rice. Interestingly, education appears to be a stronger predictor of participation in cultural dietary norms than American or Chinese acculturation in this sample. Funding Sources: NIMHD/NIH.